Comparison of dendritic calcium transients in juvenile wild type and SOD1G93A mouse lumbar motoneurons - Quinlan, Katharina A.; Lamano, Jonathan B.; Samuels, Julienne; Heckman, C. J. (Frontiers in Cellular Neuroscience, 2015)
Previous studies of spinal motoneurons in the SOD1 mouse model of amyotrophic lateral sclerosis have shown alterations long before disease onset, including increased dendritic branching, increased persistent Na+ and Ca2+ currents, and impaired axonal transport. In this study dendritic Ca2+ entry was investigated using 2 photon excitation fluorescence microscopy and whole-cell patch-clamp of juvenile (P4-11) motoneurons. Neurons were filled with both Ca2+ Green-1 and Texas Red dextrans, and line scans performed throughout. Steps were taken to account for different sources of variability, including 1) dye filling and laser penetration, 2) dendritic anatomy, and 3) the time elapsed from the start of recording. First, Ca2+ Green-1 fluorescence was normalized by Texas Red; next, neurons were reconstructed so anatomy could be evaluated; finally, time was recorded. Customized software detected the largest Ca2+ transients (area under the curve) from each line scan and matched it with parameters above. Overall, larger dendritic diameter and shorter path distance from the soma were significant predictors of larger transients, while time was not significant up to 2 hours (data thereafter was dropped). However, Ca2+ transients showed additional variability. Controlling for previous factors, significant variation was found between Ca2+ signals from different processes of the same neuron in 3/7 neurons. This could reflect differential expression of Ca2+ channels, local neuromodulation or other variations. Finally, Ca2+ transients in SOD1G93A motoneurons were significantly smaller than in non-transgenic motoneurons. In conclusion, motoneuron processes show highly variable Ca2+ transients, but these transients are smaller overall SOD1G93A motoneurons.